Eksperimen Pencampuran Limbah Ampas Kopi Sebagai Material Utama - Theresia Tifanny; Guguh Sujatmiko; Hairunnas (CandraRupa : Journal of Art, Design, and Media, 2025)
In 2022, Indonesia experienced an increase in coffee production with 794.8 thousand tons. In Surabaya itself, according to data from the Surabaya city government in 2023, there are 175 cafes in Surabaya. With the increase in cafes and coffee production, coffee grounds waste has also increased. Coffee grounds waste itself if directly disposed of in the environment will damage the environment because coffee grounds contain harmful ingredients. So that coffee grounds waste itself needs to be reprocessed and has a great opportunity because there is still little processing of coffee grounds into useful products. Product development from coffee grounds needs to show the unique characteristics of coffee grounds. To show the characteristics of coffee grounds, the method that can be done is through lighting. Through lighting the characteristics of coffee grounds in the form of powder can be seen through the light exposed to the surface of the coffee grounds material. The research method used is experimentation, namely observation for the right treatment for coffee grounds, experiments to find out the right lighting contrast, and characteristic studies for coffee grounds with light sources. The result of the research conducted is an experiment that best shows the characteristics of coffee grounds seen with the help of a light source. This research is expected to increase the usability of coffee grounds waste.